Interpretation of Waqf Distribution Verse in Islamic Economic Perspective - Lubis, Nurhayati; Sunandar, Heri (International Journal Labs, 2023)
Islamic economics is an economy that originates from the Al-Quran and Hadith. Its main goal is Rahmatal Lil Alamin, which highly upholds the values ??of justice and equality among human beings. Wealth is a deposit that God has given us to meet life's needs. Besides that, the assets we have also have other people's shares in them, so in distributing these assets, we need means to make it happen, one of which is by way of distributing Waqf. So in its implementation, we have to learn the rules and laws of Islam. This study discusses the verses of the Koran regarding distribution, endowments, hadiths related to endowments, terms and pillars of Waqf, waqf assets, utilization of waqf assets, productive endowments from an Islamic economic perspective, and finally, the distribution of endowments. This research uses qualitative research with the type of library research used to collect data from written sources such as books, journals, and other sources related to the distribution of Waqf. In the results of this study, it is known that Waqf is a fiscal policy instrument besides zakat, Waqf is also not only in the form of assets such as land and other buildings, but there is also Waqf in the form of money, so if it is used and managed correctly, it will make an excellent contribution to welfare and economic development ummah.